Advances in the synthesis of nitrogen-containing heterocyclic compounds by in situ benzyne cycloaddition. Issue 12 (13th March 2023) - Yu, Hui; Xu, Feng
Abstract : Benzyne is a relatively active intermediate, which can be used to construct diverse compounds with complex structures and potential applications via the cyclization reaction of benzyne generated in situ from various precursors. Abstract : Nitrogen-containing heterocyclic compounds are prevalent in various natural products, medicines, agrochemicals, and organic functional materials. Among strategies to prepare nitrogen-containing heterocyclic compounds, pathways involving benzyne intermediates are attractive given that they can readily assemble highly diverse heterocyclic compounds in a step-economical manner under transition-metal-free conditions. The synthesis of nitrogen-containing heterocyclic compounds from benzyne intermediates offers an alternative strategy to the conventional metal-catalyzed activation approaches. In the past years, chemists have witnessed the revival of benzyne chemistry, mainly attributed to the wide application of various novel benzyne precursors. The cycloaddition of benzynes is a powerful tool for the synthesis of nitrogen-containing heterocyclic compounds, which can be constructed by [ n + 2] cyclization of benzyne intermediates in situ generated from benzyne precursors under mild reaction conditions. This review focuses on the application of cycloaddition reactions involving in situ benzynes in the construction of various nitrogen-containing heterocyclic compounds.